(3GdSMQ hGdTYQs - (3eMeO Hf YHO Gddg Hf SYjO GdSdeGfj GddhTj GdCUd, GdZQfGWj GdCfOdSj, CHh YHO Gddg, GdTgjQ HdSGf GdOjf GHf GdNWjH,J (B776 (3g` s
(3ChdgG (B:s
(3hHYO aEfi edG ajV Gddg efi GdCOH eMdi SeGJgG hfGTQ QbegG HYO eeGJgG s
(3BNQgG (B:s
(3hbhd CHj GdMSf eYQha EMPQ YOhc hGMPQ UOjbc ced GdJbjjO HMeO Gddg hUdi Gddg Ydi ehdGfG eMeO s
(3HgG fXGe GdJYbjHIs
(3HgG fXGe GdJYbjHIs
(3fSNI CNQi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs